Efektivitas Edukasi Kesehatan Penggunaan Phantom Gigi terhadap Pengetahuan tentang Perilaku Menggosok Gigi pada Anak - Irma, Ade Irma; Muhammad Iqbal S; Cut Oktaviyana (2025)
problems. One way to minimize these problems is to conduct health education activities using teaching aids such as dental phantoms to improve knowledge about proper tooth brushing techniques. The use of dental phantoms is more effective for children because it involves a visual approach and hands-on practice, making it easier for them to understand. The purpose of this study was to determine the effect of the effectiveness of dental phantom health education on knowledge about tooth brushing behavior in children. The research design is quasi-experimental with a one-group pretest-posttest design. The population in this study consisted of all 25 students in grades V, with a sampling technique of total sampling. The data collection instrument used a questionnaire about knowledge of tooth brushing behavior. This research was conducted at Public Elementary School Ujong Kuta Darussalam Aceh Besar from May 23 to June 2, 2025. The results showed that the effect before and after dental phantom use health education on knowledge about toothbrushing behavior obtained a p-value of 0.000. The conclusion of this study is that there is an effect before and after health education on the use of dental phantoms on knowledge about toothbrushing behavior in children at Public Elementary School Ujong Kuta Darussalam Aceh Besar.